Material Management Systems in Building Projects: Status and Influencing Factors - Sharma, Mahesh (Mid-West University Journal of Engineering & Innovation, 2025)
Material management plays a critical role in construction projects, significantly influencing time, cost, and quality. Inefficient material management often results in delays, as evidenced by a study of 15 government construction projects in Surkhet district under the Federal Project Implementation Unit (FPIU). The study utilized surveys, field visits, key informant interviews, and document review and Relative Importance Index (RII) is used for ranking of the variables. Findings revealed that most projects relied on manual record-keeping, with 60% not using modern material management software, 76% failing to prioritize material management, and 84% lacking automated loading and unloading systems. Only 64% reported having proper storage systems, and while 71% emphasized material quality, field observations contradicted their claims, showing a complete lack of modern MMS adoption. The study identified 47 influential factors across eight groups, with RII values exceeding 50%, underscoring their impact on material management systems (MMS). Key issues included inadequate use of ICT, lack of prioritization, and minimal automation. Disparities in perceptions were noted between clients, consultants, and contractors regarding knowledge and priority of MMS. The study recommends adopting ICT-based systems, improving procurement regulations, and enhancing material management practices to address these shortcomings, ultimately ensuring efficient and effective project execution.